2021
DOI: 10.1002/andp.202100402
|View full text |Cite
|
Sign up to set email alerts
|

Optical Sorting of a Plasmonic or Dielectric or Chiral Mie Object Using a Single Metasurface

Abstract: Identifying an object, be it of dielectric or plasmonic or chiral nature, by only using light beam is familiarized as optical sorting. As far as is known, a single optical setup is not reported so far, where these three different kinds of Mie sized particles can exhibit completely distinct behaviors. Chemical-based sorting of these various types of particles is still considered as a notable industrial problem due to the use of very expensive chemicals. This work presents a novel all-optical technique to distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The spin angular momentum of the output beam is defined by the metasurface, which offers extra control freedom for the microparticles. Additionally, optical sorting technology is proposed based on SPP metasurface, which can sort nano-objects based on their material properties, as shown in Figure d . The metasurface consists of double-lined gold nanostructures, which form a complex plasmonic field for optical sorting.…”
Section: Applications Of Metasurface Optical Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The spin angular momentum of the output beam is defined by the metasurface, which offers extra control freedom for the microparticles. Additionally, optical sorting technology is proposed based on SPP metasurface, which can sort nano-objects based on their material properties, as shown in Figure d . The metasurface consists of double-lined gold nanostructures, which form a complex plasmonic field for optical sorting.…”
Section: Applications Of Metasurface Optical Sensorsmentioning
confidence: 99%
“…(d) Particle sorting based on material properties using a metasurface. Reprinted with permission from ref . Copyright 2021 Wiley-VCH.…”
Section: Applications Of Metasurface Optical Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that our force value is in the range of 10 −19 N for single unit cell, which can be seen insignificant to propel our QIMA solar sail. However, the light intensity used is 1(Vm), but we know that force and light intensity has a directly proportional relationship, which implies that our solar sail will show significant force with a higher rate of light intensity [ 77–80 ] during the real world scenarios. Moreover, it can be observed that the force presented for our array structure is “10” times greater.…”
Section: Analysis and Discussion Of The Resultsmentioning
confidence: 99%
“…, but we know that force and light intensity has a directly proportional relationship, which implies that our solar sail will show significant force with a higher rate of light intensity [77][78][79][80] during the real world scenarios. Moreover, it can be observed that the force presented for our array structure is "10" times greater.…”
Section: Flexible Properties Of the Unit Cell With Mechanical Stressmentioning
confidence: 99%